Ocorrência de Meloidogyne enterolobii Yang & Eisenback, no município de Uberlândia, Minas Gerais, Brasil - Almeida, Eduardo José [UNESP]; Santos, Jaime Maia [UNESP] (My University, 2011)
Meloidogyne enterolobii Yang & Eisenback (Sin.: M. mayaguensis Rammah & Hirschmann), poliphagous plant parasitic nematode, has been reported causing hard damage in several plant species in Brazil. This communication represents the first occurrence of this nematode in the municipality of Uberlândia, Minas Gerais State, Brazil.
Occurrence of Meloidogyne enterolobii in the municipality of Uberlândia, state of Minas Gerais, Brazil
Keywords: Nematology; Plant pathology; Rot knot nematode